Levels and related factors of occupational stress among nurses: hospital-based evidence from China, 2023 - Zhong, Xiaoying; Zeng, Yan; Peng, Lin; Li, Xixi; Jia, Yuanli; Pan, Changqing; Wang, Bangjun (Frontiers in Psychology, 2025)
BackgroundChina’s birth rate continues to decline, reaching only 6.39% in 2023. In light of this trend, hospitals may need to reassess their allocation of resources, including funding, staffing, and facilities. Nurses may face job insecurity and uncertainty regarding their roles, which could prompt some to consider transitioning to different specialties. This study aimed to investigate the levels of occupational stress among nurses in the context of low fertility in China in 2023 and to identify the factors contributing to this stress. In addition, the study sought to explore the relationship between family dysfunction, low fertility rates, and occupational stress levels.MethodsThis descriptive cross-sectional study involved 270 nurses working in hospitals, who were recruited between December 2023 and January 2024 through a Chinese free web-based platform (Sojump) to complete online questionnaires. In addition to demographic information, the Nursing Job Stressors Scale (NJSS) and the Family APGAR Index were utilized for data collection. The data were analyzed using descriptive and inferential statistics, including correlation and multiple linear regression analysis. For continuous variables, the mean, standard deviation (SD), median, and interquartile range were reported, while counts and percentages were used for categorical variables. The independent t-test and one-way analysis of variance were employed for univariate analysis. Multiple linear regression was utilized for multivariate analysis. A p-value of less than 0.05 was considered statistically significant.ResultsThe participants’ average scores for the NJSS and Family APGAR Index were 1.76 ± 0.58 and 6.35 ± 3.30 points, respectively. In addition, workload and time pressure were rated highest among the sub-scales of the NJSS. The top five job stressors for nurses were Q3 (Wages and other benefits are low), Q1 (The social status of nursing is too low), Q5 (Frequent shift work), Q12 (Too much useless paperwork), and Q16 (Fear of mistakes and accidents at work). The score of the Family APGAR Index demonstrated a negative correlation with occupational stress (r = −0.19, p < 0.001). The results of the multiple linear regression analysis showed that a high level of worry about losing one’s job (SE = 0.044, β = 0.152, t = 2.567, p = 0.011) and poorer family APGAR scores (SE = 0.035, β = −0.202, t = −3.406, p < 0.001) were associated with higher NJSS scores.ConclusionThe nurses reported experiencing a moderate level of occupational stress in the context of low fertility in China. The key predictors of occupational stress among the nurses included concerns about job security and the Family APGAR classification. Implementing fair compensation and providing more effective family-oriented support programs are essential for reducing occupational stress among nurses.